Penn World Table 7.0: Are the data flawed? (2013)
PWT 7.0 data deviate substantially from PWT 6.3 data because the benchmarked prices for 1970 to 1996 used in PWT 6.3 were entirely discarded. PWT 7.0 data are unreliable and appear to be much less accurate than PWT 6.3 data.